Reboxetine Improves Auditory Attention and Increases Norepinephrine Levels in the Auditory Cortex of Chronically Stressed Rats - Pérez-Valenzuela, Catherine; Gárate-Pérez, Macarena F.; Sotomayor-Zárate, Ramón; Delano, Paul H.; Dagnino-Subiabre, Alexies (Frontiers in Neural Circuits, 2016)
Chronic stress decreases GABA release in the primary auditory cortex (A1) and impairs auditory attention in rats. On the other hand, monoamines regulate neurotransmission in A1 during stress responses. In this context, the first aim of this study was to determine whether chronic stress affects monoamines levels in A1. Male Sprague-Dawley rats were subjected to chronic stress (restraint stress) and monoamines levels were measured by HPLC-electrochemical detection. Chronically stressed rats had lower levels of norepinephrine (NE) in A1 than did controls, while chronic stress did not affect serotonin (5-HT) and dopamine (DA) levels. The second aim was to evaluate the effects of reboxetine (a selective NE reuptake inhibitor drug) on auditory attention and NE levels in A1. Rats were trained to discriminate between two tones of different frequencies in a two-alternative choice task (2-ACT), a behavioral paradigm to study auditory attention in rats. Trained animals that reached a performance of ≥ 80% correct trials in the 2-ACT were randomly assigned to control and stress experimental groups. To analyze the effects of chronic stress on the auditory task, trained rats of both groups were subjected to fifty 2-ACT trials one day before and one day after of the stress period. A difference score was determined by subtracting the number of correct trials after the stress protocol from those before. Both auditory attention and NE levels in A1 were higher in stressed rats treated with reboxetine than in vehicle-treated animals. Our results suggest that NE plays a key role in A1 and attention of stressed rats through tone discrimination.